Implikasi Pembubaran Partai Politik terhadap Organisasi Sayap - Albab, Biantara (Universitas Batanghari Jambi, 2024)
One of the privileges afforded to political parties is the establishment of affiliated wing organizations, which play a crucial role in fostering party cadre. However, the legal framework governing these Organizational Wings of Political Parties remains insufficient, primarily addressed in Article 12 letter j of Law Number 2 of 2008 concerning Political Parties. Conversely, within this legislation, provisions exist for the dissolution of political parties. Thus, it prompts inquiry into whether such dissolution also extends to the affiliated wing organizations of political parties. This research aims to explore the ramifications of political party dissolution on these Organizational Wings of Political Parties, employing a normative juridical method integrating statutory and conceptual analyses. The findings indicate that the dissolution of political parties inevitably leads to the dissolution of their respective Political Party Wing Organizations. This conclusion rests on several grounds. Firstly, the existence of Political Wings Organization derives directly from the political party itself. Secondly, the absence of clear-cut regulations pertaining to the Organizational Wings of Political Parties, limited solely to the Law on Political Parties, distinguishes them from Community Organizations. Thirdly, the regulations governing Wing Organizations are contingent upon the bylaws of political parties and align with the shared objectives and aspirations of a Wing Organization and its parent political party, centered around a unified vision and mission.